2021
DOI: 10.3389/fcvm.2021.668532
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota and Atherosclerosis—Focusing on the Plaque Stability

Abstract: Cardiovascular diseases (CVDs) are major causes of mortality and morbidity in the modern society. The rupture of atherosclerotic plaque can induce thrombus formation, which is the main cause of acute cardiovascular events. Recently, many studies have demonstrated that there are some relationships between microbiota and atherosclerosis. In this review, we will focus on the effect of the microbiota and the microbe-derived metabolites, including trimethylamine-N-oxide (TMAO), short-chain fatty acids (SCFAs), and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 49 publications
(41 citation statements)
references
References 204 publications
(230 reference statements)
0
40
0
1
Order By: Relevance
“…The presence of microorganisms in the atheroma plaque is well established, and some studies have shown that the abundance of certain phyla could correlate with plaque stability and overall inflammation [ 346 , 347 ]. For instance, bacterial DNA from pathogenic families, such as Helicobacteraceae or Neisseriaceae , has been shown to be more abundant in plaques of symptomatic patients [ 348 , 349 ]. Nevertheless, these results need to be corroborated in larger studies.…”
Section: Microbiotamentioning
confidence: 99%
“…The presence of microorganisms in the atheroma plaque is well established, and some studies have shown that the abundance of certain phyla could correlate with plaque stability and overall inflammation [ 346 , 347 ]. For instance, bacterial DNA from pathogenic families, such as Helicobacteraceae or Neisseriaceae , has been shown to be more abundant in plaques of symptomatic patients [ 348 , 349 ]. Nevertheless, these results need to be corroborated in larger studies.…”
Section: Microbiotamentioning
confidence: 99%
“…These differences may be partially explained by the specific mouse models (high-fat diet versus high-fat diet plus surgical implantation of perivascular carotid collars) or the experimental time lines used [ 18 , 22 ]. Other potential explanations are differences in food compositions or microbiota secondary to the specific animal husbandry conditions [ 54 , 55 ]. Several studies have demonstrated a relationship between microbiota and atherosclerosis [ 54 , 55 ].…”
Section: Discussionmentioning
confidence: 99%
“…Other potential explanations are differences in food compositions or microbiota secondary to the specific animal husbandry conditions [ 54 , 55 ]. Several studies have demonstrated a relationship between microbiota and atherosclerosis [ 54 , 55 ]. Our current data show that changes in the metabolic state (hyperlipidemia versus hyperglycemia) have an impact on plaque stability, supporting that additional factors impact the role of hypercoagulability in atherosclerosis.…”
Section: Discussionmentioning
confidence: 99%
“…Gut bacteria of taxa Erysipelotrichia produce TMA following choline metabolization, thus decreasing the bioavailability of this macronutrient and increasing the portal influx of TMA and its conversion to trimethylamine N-oxide (TMAO). This small metabolite [ 642 , 643 , 644 , 645 , 646 , 647 , 648 ] is associated with atherosclerosis and cardiovascular complications, including myocardial infarction and stroke [ 646 , 649 , 650 , 651 , 652 ]. In addition, increased TMAO levels correlate with the presence of type 2 diabetes mellitus, glycemic control in type 2 diabetes mellitus, its complications, and steatogenic effects [ 653 , 654 , 655 , 656 , 657 , 658 , 659 ].…”
Section: Intestinal Barrier Features In Nafldmentioning
confidence: 99%